The Economic Lifeline: Quantifying AI's Impact on Hospital Readmission Savings - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The Economic Lifeline: Quantifying AI's Impact on Hospital Readmission Savings The challenge of hospital readmissions—when a patient returns to the hosp...
Keywords: Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care; Machine Learning